2019
DOI: 10.1515/hc-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and fungicidal activity of novel imidazo[4, 5-b]pyridine derivatives

Abstract: A series of novel imidazo[4,5-b]pyridine derivatives were synthesized and their structures were characterized by NMR spectroscopy, mass spectrometry and elemental analysis. The results of bioassays showed that some compounds exhibit good fungicidal activity against Puccinia polysora In particular, compound 7b showed an EC50 value of 4.00 mg/L, which was comparable with that of tebuconazole. Besides, preliminary structure-activity relationship was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Fungicides have been used in agriculture for well over a century [78]. The corresponding market has been dominated by stobilunis, triazoles and amides [79]. However, resistance to many of the most effective fungicides has emerged.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Fungicides have been used in agriculture for well over a century [78]. The corresponding market has been dominated by stobilunis, triazoles and amides [79]. However, resistance to many of the most effective fungicides has emerged.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The derivatives of imidazo [4,5-b] pyridine is being synthesized by the standard protocol as demonstrated with the earlier literature. [23,24] In our attempt to synthesize novel derivatives of 7-substituted-1H-imidazo [4,5-b]pyridine, we first prepared 7bromo-1H-imidazo [4,5-b]pyridine 2 as the scaffold and then obtained diverse analogs from 1H-imidazo [4,5-b]pyridine core moiety through C(sp 2 )À C(sp 2 ) cross-coupling reactions. Scheme 1 represent a detailed synthesis of 7-aryl-1Himidazo [4,5-b]pyridines 4(a-j), which is depicted below.…”
Section: Chemistrymentioning
confidence: 99%
“…Wu et al [103] have synthesized imidazo [4,5-b]pyridine derivatives (46 a-j, 47 a-b, and 48 a-d) and evaluated the antifungal activity against P. polysora (Figure 35). The results of bioassays revealed that some compounds (46 e, 46 g-j, and 47 a-b) showed good antifungal activity (inhibitory rates: 72 %-100 %) at the concentration of 500 mg/L.…”
Section: Plant Antifungal Agentsmentioning
confidence: 99%
“…Wu et al [103] . have synthesized imidazo[4,5‐b]pyridine derivatives ( 46 a – j , 47 a – b , and 48 a – d ) and evaluated the antifungal activity against P. polysora (Figure 35).…”
Section: Bicyclic Compoundsmentioning
confidence: 99%